Trepadeiras ornamentais do cerrado (2004). - RAMALHO, C. L. (2004)
Conhecer para preservar; Apocynaceae; Bignoniaceae; Combretaceae; Convolvulaceae; Cucurbitaceae; Dilleniaceae; Dioscoreaceae;Malpighiaceae;Menispermaceae; Passifloraceae; Sapindaceae; Verbenaceae; Vitaceae.